Modelled distributions and conservation status of the wild relatives of chile peppers (Capsicum L.). Issue 2 (17th November 2019) - Khoury, Colin K.; Carver, Daniel; Barchenger, Derek W.; Barboza, Gloria E.; van Zonneveld, Maarten; Jarret, Robert; Bohs, Lynn; Kantar, Michael; Uchanski, Mark; Mercer, Kristin; Nabhan, Gary Paul; Bosland, Paul W.; et al.
Abstract: Aim: To fill critical knowledge gaps with regard to the distributions and conservation status of the wild relatives of chile peppers ( Capsicum L.). Location: The study covered the potential native ranges of currently recognized wild Capsicum taxa, throughout the Americas. Methods: We modelled the potential distributions of 37 wild taxa in the genus, characterized their ecogeographic niches, assessed their ex situ and in situ conservation status, and performed preliminary threat assessments. Results: We categorize 18 of the taxa as "high priority" for further conservation action as a consequence of a combination of their ex situ and in situ assessments, 17 as "medium priority, " and two as "low priority." Priorities for resolving gaps in ex situ conservation were determined to be high for 94.6%, and medium or high with regard to increased habitat protection for 64.9% of the taxa. The preliminary threat assessment indicated that six taxa may be critically endangered, three endangered, ten vulnerable, six near threatened and 12 least concern. Main conclusions: Taxonomic richness hot spots, especially along the Atlantic coast of Brazil, in Bolivia and Paraguay, and in the highlands of Colombia, Ecuador, Peru and Venezuela, represent particularly high priority regions for further collecting for ex situ conservation as well as for enhanced habitat conservation.